Professional Oracle WebLogic Server - Patrick, Robert (Indianapolis, IN : Wiley Pub., 2010)
Provides information on developing and deploying WebLogic Server applications.
"Wrox programmer to programmer"--Cover.
Includes index.
rua 17/10/13
Loans
Keywords: Web servers; Application software -- Development; Java (Computer program language)